The Impact of a Dissonance-Based Eating Disorders Intervention on Implicit Attitudes to Thinness in Women of Diverse Sexual Orientations - Kant, R. M. Naina; Wong-Chung, Agnes; Evans, Elizabeth H.; Stanton, Elaine C.; Boothroyd, Lynda G. (Frontiers in Psychology, 2019)
Dissonance-based body image programmes have shown long term effectiveness in preventing eating disorders and reducing risk factors for eating disorders in women. Here we report on the potential for one such intervention to impact on implicit attitudes towards thinness as well as an explicit measure of eating attitudes, across a sexually diverse group of young women. The Succeed Body Image Programme was adapted to remove heteronormative assumptions and was delivered to a final sample of 56 undergraduate women who reported their sexual orientation as either ‘predominantly heterosexual’ (our term; 1 or 2 on a 1-7 Kinsey scale, N=38) or non-heterosexual (3-7 on the Kinsey scale, N=18). Before and after the intervention, they completed the Eating Attitudes Test-26, and an associative reaction time task based on the Implicit Association Test, in which bodies of low and higher weight were paired with socially desirable or undesirable traits. 37 predominantly heterosexual women completed a control intervention in which they read NHS leaflets on eating disorders and healthy weight. Results showed that the intervention made predominantly heterosexual participants less prone, versus control, to associating thinness with positive traits on the IAT and all women completing the intervention reported a lower level of disordered eating attitudes at post- than pre-test. Non-heterosexual women, however, showed a non-significant increase in thin-bias on the IAT, perhaps due to their low baseline. These results imply that intensive dissonance-based programmes can change attitudes at the automatic, implicit level as well as merely giving women tools to overcome those implicit attitudes.